The Influence of Multicultural Values in Civics Education on MI Students' Tolerance and Nationalism - Riris Fatimah Nur Jannah; Murfiah Dewi Wulandari (Jurnal Elementaria Edukasia, 2025)
Learning in Madrasah Ibtidaiyah or elementary schools prioritizes character education, which can be obtained in various ways, one is through the approach of multicultural values ​​in PPKn learning. This study aims to empirically test the influence of multicultural values ​​in PPKn learning on the behavior of tolerance and love of the homeland in students of Madrasah Ibtidaiyah (MI) Muhammadiyah Bloran located in Kerjo District, Karanganyar Regency, Central Java Province, which has implemented Pancasila and Citizenship Education (PPKN) learning in Unit 3 with the title "Building Identity in Diversity." The type of research used is quantitative research with methods or data analysis using regression analysis. The subjects in this study were 4th-grade students consisting of 72 students at MI Muhammadiyah Bloran. The results obtained in this study indicate that multicultural values ​​have an influence but are not too significant on tolerance behavior in students. Multicultural values ​​have little impact on students' love of the homeland. The research that has been conducted expects to determine the influence of multicultural values ​​on the behavior of tolerance and love of the homeland so that multicultural education can support character education in learning in madrasah ibtidaiyah and elementary schools. It can positively influence the instillation of multicultural values ​​​​in the behavior of tolerance and love of the homeland for students, especially at MI Muhammadiyah Bloran